MANAJEMEN WAKTU TERHADAP KUALITAS BELAJAR SISWA DI MTS ANWARUL HASANIYAH - A. Rapizur Rahman; Ahmad Muhaimin; Ahmad Sauqi; Al Amin; Syahrani Syahrani (CV. ADIBA ASIHA AMIRA, 2023)
Time management is managing time so that the time we use is not wasted. Many students cannot divide their time well between time for studying, time for relaxing, and time for other activities. Time management is an internal factor, namely a process of managing yourself. The role of time management is very necessary in learning activities, because time management is one of the internal factors that influences learning. Apart from study time management, parental participation is also a factor that supports the success of good study achievement. Students’ understanding of time management will form a disciplined person. Students must practice managing and allocating time every day. Good time management allows students to separate learning activities from personal activities. This research aims to find out about Time Management on the Quality of Student Learning at MTs Anwarul Hasaniyah.